How Does Problem Based Learning Work on Students' Writing Ability? (CAR Study) - Binsar Maruli Tua Pakpahan; Noor Aziz; Ni Putu Juliani Lestari Dewi; Devin Mahendika (Journal of English Culture, Language, Literature and Education, 2023)
The problem-based learning method is one of the methods that can be applied in EFL classes, especially for students' writing skills, so that it can create a pleasant learning atmosphere and make learning more active in classroom learning activities. The problem-based learning model is one of the learning models that can shape scientific behavior, social actors, and develop students' curiosity. Learners are initially faced with a problem, then followed by a student centered information search process. Seeing the importance of this method, this study aims to see the extent to which the PBL method can improve students' ability to write Narrative text. With Classroom Action Research design, this study was applied to 20 students of class X. In collecting data, tests were used to obtain an overview of student achievement, each of which was given in each cycle. The results of this study show that PBL can improve students' narrative text writing skills, this can be seen from the percentage of student results in each cycle. In addition to making the classroom atmosphere active and participatory, PBL also makes students think more critically in solving their problems. Students are required to be able to solve their problems both individually and in groups. Seeing the important role of this PBL method, the results of this study can be used as starting points or corrections for further research